Impact of Financial Literacy, Lifestyle, and Paylater Use on Students’ Financial Planning - Nur Anissah Barim; Asriany; Sahrir (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
The development of digital financial services such as paylater is increasingly being used by students, but this is often not balanced with adequate financial literacy and wise lifestyle management. This condition has the potential to cause personal financial problems and disrupt students' financial planning. This study aims to analyze the influence of financial literacy, lifestyle, and paylater usage decisions on the financial planning of students at Andi Djemma University in Palopo City. This study uses a quantitative method with total sampling technique on 95 respondents, as well as multiple linear regression analysis using SPSS software. The results show that financial literacy has a significant positive effect on financial planning, while lifestyle and paylater usage do not have a significant effect. Simultaneously, the three variables have a significant effect with a contribution of 43.9%. These findings emphasize the importance of financial literacy as a major factor in supporting students' financial planning.